Development of a video analysis protocol and assessment of fall characteristics in equestrian cross-country eventing - Nylund, L. E.; Sinclair, P. J.; McLean, A. N.; Cobley, S. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Cross-country eventing is one of the highest-risk sporting activities for serious injury outcomes. This study investigated relationships between fall characteristics and high-risk falls at jumps in cross-country eventing. A video analysis protocol was systematically developed to analyze 87 video recordings of high-risk rider falls; defined as when the rider's head impacted the ground and/or where there was potential horse impact with the rider. Falls were classified according to competition type, jump type, horse-related, and rider-related factors. At least one high-risk fall characteristic was observed in 45 of 87 examined falls. Multivariable best subsets regression identified five independent variables explaining 38.4% of the variance in the number of high-risk falls. Increased likelihood of high-risk falls was associated with continuation of horse direction or speed upon rider ground impact, higher jump approach speed, changes in rider body posture upon landing, rider air jacket usage, and reduced rider fall time. The Eventing Fall Assessment Instrument (EFAI) video analysis protocol (attached as supplementary material) facilitated systematic examination of multiple characteristics associated with high-risk falls and identified likely influential characteristics. Based on EFAI and subsequent data analyses, findings suggest optimized approach speed for correct striding and take-off; jump design to enable run-out; and rider training could help reduce the occurrence of high-risk falls. Air jacket usage and their design characteristics warrant further investigation.